Screening for antimicrobial activity of crude extracts of Skeletonema costatum - R. Shanmugapriya, T.Ramanathan (Journal of Applied Pharmaceutical Science)
Various organic and aqueous extracts of Skeletonema costatum were screened for their antibacterial activities. The extracts were tested against different species of human pathogenic bacteria by the agar-solid diffusion method. Water extract of Skeletonema costatum showed maximum antimicrobial activity of 19.0 mm against Klebsiella pneumoniae and a minimum activity of 9 mm against Proteus vulgaris. All the tested microorganisms were resistant to methanol, ethanol and propanol extracts except Escherichia coli and Staphylococcus aureus which exhibited a least inhibition zone of 6.0 and 7.0 mm respectively in propanol. Acetone extract of Skeletonema costatum also showed the highest biological activity of 19.0 mm against Klebsiella pneumoniae, moderate activity of 12.0 mm against Salmonella typhi, and 11.0 mm against Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus. Sequential extract of Spirulina exhibited maximum antimicrobial activity. Inhibition zone of 23.2 mm was observed for Klebsiella pneumoniae and 14.0 mm for Proteus vulgaris.
Keywords: Skeletonema costatum, Human pathogenic bacteria, Antimicrobial activity, Phytoplankton, Microorganisms.